The Effectiveness between Using CALL with Hot Potatoes and MALL with Quizizz for Vocabulary Enhancement at MAN 2 Gresik - Silviana Putri Indah Sari; Yudhi Arifani; Candra Hadi Asmara (Universitas Muhammadiyah Gresik, 2022)
This study has the purpose to know which are more effective used weather using Hot Potatoes for CALL(computer-assisted language learning) and Quizizz for MALL(mobile-assisted language learning) to improve vocabulary enhancement in a learning among 11 grade students in Gresik, Indonesia especially at MAN 2 Gresik. this study was used a quantitative research experiment with quasi experiment design. This research experiment was used a sample size of 49 students of 11 grade. The students were divided into two groups that were picked used purposive sampling technique or determine the sample with used a certain consideration. The two group were 11 MIPA 1 taught with CALL media and 11 MIPA 3 taught with MALL media. Both group did pre-test treatment and post-test in the same time, also the got same duration and material when did treatment. The finding shown revealed that there is a significant difference in vocabulary enhancement between students who were taught using CALL and MALL. Then, after the researcher calculate about the effect size, the result shown the data was 0.3067, which means that there is a medium effect.